Collective Victimhood and Ingroup Identity Jointly Shape Intergroup Relations, Even in a Non-violent Conflict: The Case of the Belgians. Issue 3 (21st November 2017) - Jasini, Alba; Delvaux, Ellen; Mesquita, Batja
Collective victimhood is the belief that one's own group has been intentionally and undeservingly harmed by another group (Bar-Tal, Chernyak-Hai, Schori, & Gundar, 2009 ). While previous research has established the link between collective victimhood and negative intergroup behaviors, the underlying mechanism is virtually unexplored. In the current study, we test the idea that intergroup emotions play an important role, particularly for those group members who are highly identified. Whereas previous research has primarily studied collective victimhood in violent contexts, the current study focuses on its role in the intergroup relations in Belgium, known as a non-violent conflict between French and Dutch speakers. The associations between collective victimhood, intergroup emotions, and action tendencies were studied in an online survey. The sample consisted of both French-speaking and Dutch-speaking Belgians ( Ntotal = 1774). Structural equation modeling showed that collective victimhood was negatively related to intergroup affiliative emotions (i.e., sympathy) and positively to intergroup distancing emotions (i.e., anger). In addition, these relationships were stronger for participants who strongly identified with their ingroup. Furthermore, intergroup affiliative emotions positively predicted fostering contact with outgroup members, and negatively predicted the tendencies to exclude and take revenge on the outgroup; intergroup distancing emotions positively predicted outgroup exclusion and revenge, and negatively predicted fostering contact with them. The established associations were no different between the linguistic groups. Our results confirm that collective victimhood, and the emotions associated, can help to understand intergroup conflict in non-violent contexts, in addition to violent ones.